Anti Corruption Secretariat - The Expat (The Expat, 2012)
The Malaysian Anti-Corruption Commission (MACC) plays a vital role in Malaysia. This agency is tasked with the role of preventing and averting the corruption and the abuse of power in Malaysia, both in the public and private sectors. Promoting the mission, vision, and objectives of MACC is not an easy task as it faces a number of potential problems. MACC is continually seeking ways to achieve its goals within the confines of both Malaysian law and the specific MACC Act that gives the Commission its power.